Physician-Assisted Dying: A New Option In Canadian End of Life Care - Bobrowski, David; Bhatia, Faizan (The Meducator, 2016)
Healthcare in Canada is undergoing a major transformation as patients obtain the right to request for and be granted physician-assisted dying (PAD).1 This legal reform represents a paradigm shift in Canada’s approach to end of life care. In February 2015, the Supreme Court of Canada (SCC) struck down laws that made it illegal for individuals to assist others in ending their own lives. The ruling on PAD has been held in suspension for 16 months to allow for amendments to health policy.2 The SCC’s ruling only applies to competent adults with persistent, intolerable suffering, who consent to ending their lives.1 In this article, we aim to coalesce several opinions on the implementation of PAD, highlight the challenges, and critically evaluate recommendations of several policy-influencing bodies.